Faktor Risiko Epilepsi Intraktabel pada Anak dengan Epilepsi Umum - Irawan Mangunatmadja; Dina Indah Mulyani; Sudung O Pardede; Bambang Tridjadja; Harjanti F Wulandari (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Introduction: Several datas studied of intractable epilepsy risk factors areavailable in childhood epilepsy. The objectve of this reasearch to investigatethe role of early or evolution several factors on childhood with generalizedepilepsy as risk factors of intractable epilepsy. Methods: Retrospective cohort study was conducted at neurology out patient pediatric and private outpatient clinic Cipto Mangunkusumo Hospital between January 2010 to December 2013. The inclusion criteria was childhood gener-alized epilepsy with age 1 month up to 18 years old which has been treated with anti epileptic drugs for at least 6 months. Risk factors were analyzed with bivariate and multivariate analysis. Results: Prevalence of intractable generalized epilepsy is 21% of 102 subject. Bivariate analysis showed that age onset of seizure, initial seizure frequency, non-responder of early treatment, unfavorable gross motor development evo-lution and unfavorable epilepti form EEG evolution were significantly associated with intractable epilepsy. Based on multivariate analysis only non-responder of early treatment (p less than 0.001) and age onset less than 1 year old (p less than 0.001). Conclusions. Non-responder early treatment and age onset of seizure less than 1year old are strongly associated with intractable in childhood generalized epilepsy.